Comments on "assessment of amputee socket-stump-residual bone kinematics during strenuous activities using Dynamic Roentgen stereogrammetric analysis" - Eshraghi, A.; Gholizadeh, H.; Abu Osman, Noor Azuan (2011)
The design, construction, and fitting of artificial limbs remain to this day an art, dependent on the accumulated expertise of the practitioner/prosthetist. Socket fitting is cost ineffective, time consuming, and a source of inconvenience for the amputee. Stumpskin slippage within the socket can cause discomfort, internal limb pain, and eventually skin ulcers as a result of excessive pressure and shear within the socket. This study presents a new method of assessment of three-dimensional (3D) socketstump kinematics/slippage of strenuous activities using Biplane Dynamic Roentgen Stereogrammetric Analysis instrumentation. Ten below knee amputees participated in the study. A more holistic representation of the downward slippage trend of all proximal side skin markers with respect to the socket, and an even more characteristic and of higher magnitude downward-and anterioposterior slippage (maximum slippage: 151 mm for the fast-stop task and 19 mm for the step-down task) between the distal markers after impact, was possible for both tasks for all amputees. Displacement between skin-to-skin marker pairs reached maximum values of approximately 10 mm for the step-down trials and up to 24 mm for the fast stop trials. Maximum skin strain was dependent on the position of the skin markers. Distally positioned skin marker pairs demonstrated mainly anterioposterior displacement between each other (maximum relative strain: 13 to 14). Maximum relative strain for the proximal markers was 8 to 10. This highly accurate, in-vivo, patient-specific, unobtrusive dynamic information, presented using 3D visualization tools that were up to now unavailable to the clinician-prosthetist, can significantly impact the iterative cycle of socket fitting and evaluation.